Sustainable nanocomposite films based on bacterial cellulose and pullulan - Trovatti, Eliane
Bionanocomposites with improved properties based on two microbial polysaccharides, pullulan and bacterial cellulose, were prepared and characterized. The novel materials were obtained through a simple green approach by casting water-based suspensions of pullulan and bacterial cellulose and characterized by TGA, RDX, tensile assays, SEM and AFM. The effect of the addition of glycerol, as a plasticizer, on the properties of the materials was also evaluated. All bionanocomposites showed considerable improvement in thermal stability and mechanical properties, compared to the unfilled pullulan films, evidenced by the significant increase in the degradation temperature (up to 40 A degrees C) and on both Young's modulus and tensile strength (increments of up to 100 and 50%, for films without glycerol and up to 8,000 and 7,000% for those plasticized with glycerol). Moreover, these bionanocomposite films are highly translucent and could be labelled as sustainable materials since they were prepared entirely from renewable resources and could find applications in areas as organic electronics, dry food packaging and in the biomedical field.